W parku z Raymondem Rousselem – anamorfoza i ornament - Gołąb, Mariusz (Śląskie Studia Polonistyczne, 2018)
The article is devoted to the semantic and composition functions of the figure of a park/garden in Raymond Roussel’s novel Locus Solus. The issue discussed in this paper concerns a pretextual function of fictional space for the narration mode and sequential order of the novel. An attempt is made to supplement the dominant structuralist tradition of interpreting Roussel’s work, for example, with the concepts appearing in Maria Gołaszewska’s eco-aesthetic approach and Arnold Berleant’s environmental aesthetics. The proposed direction of reflections allows us to see in the rhetorical aspects of Roussel’s style, among which numerous hyperboles particularly attract the reader’s attention, a narrative method of anthropologically understood imaginary structures. These structures were based on the systems of objects, whose task, apart from rhetorical and cultural deluding, governed by the poetics of absurd, is to determine an anthropological point of observation in the very problem of visual experience connected with the walk in the park, intended by Roussel as an integral element of the plot. The article points out that the main problem of the novel is garden space seen from the perspective of visual anthropology, with the cultural pattern of an imaginary structure determined by the space. This space is given the function of disinterested narrating. According to the author of the proposed analyses, the meaning of such an understood visual metaphor is carried by two primary figures inscribed in the space of the garden: anamorphosis and ornament.